Adaptation of Australian community disaster resilience scorecard & self assessment of community disaster resilience - Mohamed Ludin, Salizar (2015)
Introduction: Community resilience is the sustained ability of a community to withstand and recover from adversity after an emergency. In preparation for the post-2015 Hyogo framework for action, countries across the globe emphasize supports to the local governments and community organizations in implementing community resilience programs (HFA 2013). Thus Public health nursing had the opportunity to increase the capacity of the disaster cycle and remain constant in the national planning framework on disaster. Despite Malaysian government has outlined the need to re-look and develop the country's sustainable disaster recovery policies and rebuilding post-disaster, the level and how to measure our community disaster resilience is unknown. Objectives: This research aims to adapt the Australian-Torrens Resilience Institute (TRI) community disaster resilience scorecard and have the basis of knowledge on Malaysian community disaster resilience and views on the prevention, preparedness, response, and recovery paradigm. Methodology: This paper is part (Phase 1- Part 1) of a bigger flood project on Community Disaster resilient. In this paper, the participatory action research design was done. Participatory work and discussion among the key persons involved in the Kelantan flood affected area to adapt the Australian Community Disaster Resilience (CDR) Scorecard by Torrens Resilient Institute (TRI, 2010) as their guideline to measure their community. The six highest flood affected areas were chosen as the study setting in this study. Result: All The four components of resilience shown in ‘caution zone’ for all six areas. It was shown that the communities need attention to monitoring and strengthen the community disaster resilience. The finding will assist in keeping safe and the national strategy by considering community safety priorities and needs in Kelantan’s flood disaster communities including communication, cooperative approaches; maximizes the opportunity to compare and add the previous study finding and lastly it will align with international activities. Conclusion: The result indicates that there is a need for a successfully used of standardized resilience scorecard in our setting. It will indicate on the increased quality, quantity and capability of healthcare and emergency preparedness across Malaysia and it enables practitioners to make necessary reallocations of aid toward preparedness across Malaysia and it enables practitioners to make necessary reallocations of aid toward the community.